2003
DOI: 10.2337/diacare.26.4.1176
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Severe Hypoglycemia Requiring Emergency Treatment in Type 1 and Type 2 Diabetes

Abstract: OBJECTIVE -To determine the incidence, predisposing factors, and costs of emergency treatment of severe hypoglycemia in people with type 1 and type 2 diabetes. RESEARCH DESIGN AND METHODS-Over a 12-month period, routinely collected datasets were analyzed in a population of 367,051 people, including 8,655 people with diabetes, to measure the incidence of severe hypoglycemia that required emergency assistance from Ninewells Hospital and Medical School (NHS) personnel including those in primary care, ambulance se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

38
378
5
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 530 publications
(429 citation statements)
references
References 24 publications
(18 reference statements)
38
378
5
8
Order By: Relevance
“…reported that ~ 30% were referred to hospitals 14. A retrospective analysis of emergency care in a population of nearly 400 000 inhabitants in the UK reported a higher rate of referrals (59%) to the hospital emergency service 27, but in that study, a glucose value < 3.5 mmol/l and parenteral therapy was an inclusion requirement.…”
Section: Discussionmentioning
confidence: 78%
“…reported that ~ 30% were referred to hospitals 14. A retrospective analysis of emergency care in a population of nearly 400 000 inhabitants in the UK reported a higher rate of referrals (59%) to the hospital emergency service 27, but in that study, a glucose value < 3.5 mmol/l and parenteral therapy was an inclusion requirement.…”
Section: Discussionmentioning
confidence: 78%
“…There is evidence that frail older patients are prone to severe hypoglycaemia [7,8,23]. Our data indicate that dementia is likely to be an additional major independent contributor to this excess risk with potentially adverse consequences for the individual and the community.…”
Section: Discussionmentioning
confidence: 67%
“…2) were extracted from NHS data 12, two publications 4, 11, and National Institute for Health and Care Excellence (NICE) quality standards 13. The publication by Leese et al .…”
Section: Methodsmentioning
confidence: 99%
“…The publication by Leese et al . 11 is the only publication to give absolute numbers of people using an ambulance, accident and emergency and hospital after severe hypoglycaemic episodes. The publication by Brod et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation